Aspiciliella pakistanica a new lichen species (Megasporaceae, Pertusariales, Ascomycota) from Pakistan - Habib, Kamran; Firdous, Qudsia; Sohrabi, Mohammad; Khalid, Abdul Nasir (Phytotaxa, 2021)
A new species in Megasporaceae, Aspiciliella pakistanica is described and illustrated from Pakistan. A comparative morpho–anatomical study and ITS–based molecular analysis confirmed its position within the recently resurrected genus Aspiciliella. The taxon is characterized by whitish–grey thalli having large and thick areoles without pale lines on the surface, and a discontinuous algal layer arranged in groups of vertical rows. Its positioning in a separate branch in the phylogenetic tree also makes it distinct from the other known species of the genus.